Designing a strategic supply chain performance measurement system: A conceptual framework with a holistic approach - (:unkn) unknown (My University, 2005)
The purpose of the presented article is to build a comprehensive and applicable supply chain performance measurement framework within holistic approach. Special emphasis has been given to analyzing and constructing of performance measurement framework in respect to company supply chain strategy. In this regard, attention has been called to the alignment between performance measures and the organizational objectives and strategies.
Keywords: Balanced scorecard; Logistics; Performance measurement; Supply chain